Pemanfaatan Limbah Kulit dan Bonggol Nanas Berbagai Varietas sebagai Substrat Fermentasi Tepache Menggunakan CRD - Tanty Sulistiani Widodo; Lina Herlinawati Herlinawati; Sani Mustikawati Mustikawati; Gita Amalia Zukhruf (Ma'soem University, 2026)
Pineapple peel and core waste are abundant agro-industrial by-products that have not been optimally utilized. These materials are known to contain sugars, organic acids, and natural microflora, making them potential substrates for fermentation. One traditional fermented product that can be developed from pineapple peel and core is tepache, a Mexican fermented beverage typically made from pineapple peel, water, and sugar, and naturally fermented by microorganisms present in the raw materials and environment. Differences in pineapple varieties are presumed to affect the chemical composition of the peel and core, potentially resulting in variations in fermentation characteristics and product quality. This study aimed to evaluate the potential of pineapple peel and core waste from different varieties as substrates for tepache production and to assess the effect of variety on the physicochemical and sensory characteristics of the resulting product using a Completely Randomized Design. The experiment employed a single factor, namely pineapple variety, consisting of three treatments: Belik, Queen, and Honi, each with six replications. The fermentation process was conducted under controlled conditions with uniform formulation and fermentation time. The observed parameters included total sugar content, pH value, alcohol content, and sensory attributes such as color, aroma, taste, and aftertaste. Data were analyzed using Analysis of Variance at a 95% confidence level, followed by a post hoc test to determine differences among treatments. The results showed that pineapple variety had a significant effect on total sugar, pH, alcohol content, as well as sensory attributes of color, aroma, and aftertaste. However, no significant effect was observed on taste. The Honi variety produced the highest total sugar content and pH, the Queen variety resulted in the highest alcohol content, while the Belik variety achieved the highest sensory acceptance. Therefore, pineapple peel and core waste from different varieties demonstrated strong potential as substrates for tepache fermentation.